Australia goes to Washington: 75 years of Australian representation in the United States, 1940-2015 - Lowe, David; Lee, David; Bridge, Carl (ANU Press, 2016)
Since 1940, when an Australian legation was established in Washington DC, Australian governments have expected much from their representatives in the American capital. This book brings together expert analyses of those who have served as heads of mission and of the challenges they have faced. Ranging beyond conventional studies of the Australian-United States relationship, it provides insights into the dynamics between Australian and US policymakers and into the culture of one of Australia's oldest and most important overseas missions. It provides an appreciation of the importance of the embassy and the head of mission in Washington in mediating the relationship between Australia and the United States and of their role in managing expectations in Canberra and Washington. Australia Goes to Washington also sheds new light on personal trials and achievements at the coalface of Australian-United States relations.